Vliv okrajových podmínek v metodě SPH - Halada, Tomáš; Tomáš Halada (České vysoké učení technické v Praze, 2022)
Rozvíjeným tématem je vliv realizace okrajových podmínek v bezsíťové částicové metodě Smoothed Particle Hydrodynamcis (SPH) s ohledem na problémy proudění s volnou hladinou. Práce vychází z třírozměrných simulací na komplexních geometriích výtokových objektů čerpacích a turbínových stanic řešených pomocí metody SPH. Problémy spojené s realizací okrajových podmínek motivovaly studium provedení pevných stěn i vstupů a výstupů. Na několika testovacích příkladech je zkoumán vliv pokročilých realizací okrajových podmínek pro pevné stěny a vstupy a výstupy při zohlednění vlivu volné hladiny. Mimo to je rozebírána alternativní formulace SPH metody založena na částečně Lagrangeovské a částečně Eulerovské formulaci (ALE-SPH), odstraňující některé z nedostatků klasické varianty SPH metody.

The topic is the influence of the realization of boundary conditions in the meshless particle method Smoothed Particle Hydrodynamcis (SPH) with regard to the free-surface flow problems. The work is motivated by three-dimensional simulations of discharge objects of pumping and turbine stations with complex geometries performed by SPH method. Problems associated with implementation of boundary conditions led to the study of construction of the boundary conditions for solid walls and inlets and outlets. The influence of advanced realisation of boundary conditions for solid walls and inlets and outlets is investigated on several test cases, taking into account the influence of the free surface. In addition, alternative formulation of the SPH method based on partially Lagrange and partially Eulerian description (ALE-SPH) is discussed, while it improves some of the shortcomings of the classical variant of the SPH method.
Influence of boundary conditions in SPH method
Keywords: Proudění s volnou hladinou; Smoothed Particle Hydrodynamics; okrajové podmínky; Free-surface flow; Smoothed Particle Hydrodynamics; boundary conditions